Assessing the effect of fillers on LVE properties of asphalt mastics at intermediate temperatures - Chaudhary M.; Saboo N.; Gupta A.; Hofko B.; Steineder M. (My University, 2025)
This study aims at examining the performance of asphalt mastics in the Linear Viscoelastic (LVE) domain incorporating three Indian and three Austrian fillers. The various physical, morphological, and chemical properties of the fillers were analyzed with the help of respective characterization tests. In addition to the particle size distribution curve and fineness modulus, a new parameter called Filler Grain Coefficient (FGC) has been introduced in this study to quantify the distribution of particles in the system. This paper also attempts to find a correlation between various physical parameters. There are two variables i.e., |G∗|LVE and |G∗|ratio in order to quantify the Linear Viscoelastic complex modulus. The effects of both volume and surface area of fillers have been manifested by three ratios denoted as V/FM, V/FGC, and V/RV. To compare the outcome of the study, the Strategic Highway Research Program Linear Viscoelastic strain criteria is also included, which examines the applicability of the criteria to the asphalt mastics. The research incorporates a wide range of fillers with variable properties, as confirmed by the test results. Filler parameters Rigden Voids and Filler Grain Coefficient were found to be strongly correlated with almost all physical properties. On the grounds of variation in LVEM with volume concentration of filler, the highest rank can be attributed to Red Mud and LimeStone, respectively, followed by other fillers with Marble Dust being the lowest. The reinforcing effect of fillers and higher surface area contributed to the exponential increase in |G∗|LVE, with an increase in volumetric concentration. The variation of both variables: |G∗|LVE and |G∗|ratio, presented V/FM as the most worthy parameter, as it illustrated variation at different temperatures. The Linear Viscoelastic limits obtained from the study were relatively conservative compared to those from the SHRP study, this confirms the unsuitability of applying SHRP equations to the asphalt mastics. Moreover, the relationship instigated in the study can be used to reckon the LVE strain limit and to further analyse asphalt mastics. © 2020, RILEM.